INFOSOIL - an information-reference system for soil recognition and classification in Russia - V. A. Rozhkov; S. V. Rozhkova; P. V. Kravets; D. E. Konyushkov (Бюллетень Почвенного института им. В.В. Докучаева)
INFOSOIL is a new information-reference system aimed at elaborating purposeful classifications of soils by using a definite set of soil features. The stages and procedures of this system permit to determine the maximum number of objects taking into complete account their most informative features, the method and quality of objects grouping into classes as well as to recognize newly presented soils to be classified. This system should be named as a generator or engine of soil classifications developed for different purposes; it is based on the concept of enumeration classification, thus connecting a totality of soil features to meet requirements of the soil classification. The amount of features (classifier positions) determines the maximum number of objects and brings them in correspondence. It is shown how is realized the suggested approach in practice; the position of soils in the classification system is indicated. In this paper the first INFOSOIL version (www.infosoil) is presented to show the development of its real possibilities and accessibility for users and classification authors. In the system the interfaces are envisaged with the soil-geographical database, the State register of soil resources and the Soil map, 1: 2.5 M scale. In essence the system contains the soil classification system widely adopted now (2004), the automated guide to determine the soils (2008) and creates all the conditions for its further development. INFOSOIL has being elaborated as an intellectual information system that includes the MERON system, algorithm means to create new enumeration classifications as well as to use and study the available classifications.